Confirmatory Strategic Information Technology Implementation for Building Information Modelling Adoption Model - Enegbuma, Wallace Imoudu; Aliagha, Godwin Uche; Ali, Kherun Nita; Badiru, Yusuf Yunusa (Penerbit Universiti Sains Malaysia, 2016)
Information technology (IT) developments in the construction industry require a proportionate response by construction professionals. Building information modelling (BIM) requires strategic changes to the traditional ways construction is carried out. BIM adoption in Malaysia is growing because of recent efforts to sensitise construction professionals on the need for strategic IT implementation. This paper builds on the theory of business process reengineering and computer integrated construction for a BIM adoption model. Data were collected from 352 construction professionals (architects, quantity surveyors, engineers and contractors). The data were analysed using Statistical Package for Social Sciences (SPSS) version 18 for descriptive modelling and Analysis of Moment of Structures (AMOS) version 18 for structural equation modelling. Descriptive results showed a high prevalence of the need for BIM competent professionals. Multivariate results revealed a high correlation within the measurement model for business process re-engineering and computer integrated construction. The second-order confirmatory model showed that business process reengineering and computer integrated construction had a high impact on strategic IT Implementation. Overall, the model validated the conceptual framework of the impact of strategic IT implementation on the adoption rate of BIM in the perception of construction industry professionals in Malaysia. The result denotes the first part of the full adoption model, which can be compared with the adoption rate in other countries. Subsequent research using a diverse sample selection focuses on the mediating effect of collaboration on BIM adoption.